OPAC (orange peel activated carbon) derived from waste orange peel for the adsorption of chlorophenoxyacetic acid herbicides from water: Adsorption isotherm, kinetic modelling and thermodynamic studies. (August 2018) - Pandiarajan, Aarthi; Kamaraj, Ramakrishnan; Vasudevan, Sudharshan; Vasudevan, Subramanyan
Graphical abstract: Highlights: Low-cost carbon – adsorbent was prepared from orange peel waste by simple method. The synthesised orange peel activated carbon surface area was 592.471 m 2  g −1. Adsorption mechanism and kinetics studies of highly hazardous chlorophenoxy herbicides from aqueous was studied. Maximum Langmuir capacity of 574.71 mg g −1 was achieved. Abstract: This study presents the orange peel activated carbon (OPAC), derived from biowaste precursor (orange peel) by single step pyrolysis method and its application for the adsorption of chlorophenoxyacetic acid herbicides from the water. The OPAC exhibited the surface area of 592.471 m 2  g −1, pore volume and pore diameter of 0.242 cc g −1 and 1.301 nm respectively. The adsorption kinetics and thermodynamic equilibrium modelling for all chlorophenoxyacetic acid herbicides were investigated. The various parametric effects such as pH and temperature were evaluated. A pseudo-second-order kinetic model was well fitted for all the herbicides. The Langmuir isotherm was obeyed for all the herbicides and the maximum Langmuir capacity of 574.71 mg g −1 was achieved. The thermodynamic studies revealed that the adsorption increases with increase in temperature. The results shows that the orange peel derived carbon (OPAC) as effective and efficient adsorbent material for the removal of chlorophenoxyacid herbicides from the water.